About the tendency to synchronization of the Earth and the Moon rotary movements - Kurbasova, G.S.; Rykhlova, L.V. (Кинематика и физика небесных тел, 2005)
The Hierarchical structure of the Earth–Moon system provides process of self-organizing. The principle of synchronization and symmetry of initial structure of the Earth–Moon system and the processes, breaking symmetry form the basis of self-organizing model. The theory of a nonlinear parametrical resonance allows finding the features as results of perturbation effects. In the present paper some ratio which determine stationary structure of the Earth–Moon system is given.